2016
DOI: 10.18632/oncotarget.v7i23
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A considerable proportion of the human genome consists of transposable elements, including the long terminal repeats (LTRs) of endogenous retroviruses. During evolution, such LTRs were occasionally inserted upstream of protein-coding genes, contributing to their regulation. We previously identified the LTR12 from endogenous retrovirus 9 (ERV9) as a regulator of proapoptotic genes such as TP63 or TNFRSF10B. The promoter activity of LTR12 is largely confined to the testes, silenced in testicular carcinoma, but r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
(73 reference statements)
0
23
0
Order By: Relevance
“…44 Studies have found that the oncogene CDK4, which plays a critical role in the progression of the cell cycle, is directly targeted by miR-486-5p, and mir-486-5p can inhibit non-small cell lung cancer by downregulating the expression of CDK4. 45 In this study, it was found that CDK4 was a potential target of miR-486-5p and that miR-486-5p regulated its expression by targeting the 3ʹUTR of the CDK4 gene. In addition, miR-486-5p overexpression reduced CDK4 expression, and co-transfection of shLINC011948, and miR-486-5p mimicked partially the effect of sh-LINC011948 on CDK4 protein levels.…”
mentioning
confidence: 82%
“…44 Studies have found that the oncogene CDK4, which plays a critical role in the progression of the cell cycle, is directly targeted by miR-486-5p, and mir-486-5p can inhibit non-small cell lung cancer by downregulating the expression of CDK4. 45 In this study, it was found that CDK4 was a potential target of miR-486-5p and that miR-486-5p regulated its expression by targeting the 3ʹUTR of the CDK4 gene. In addition, miR-486-5p overexpression reduced CDK4 expression, and co-transfection of shLINC011948, and miR-486-5p mimicked partially the effect of sh-LINC011948 on CDK4 protein levels.…”
mentioning
confidence: 82%
“…34,39 We investigated if cell surface expression of PD-L1 in prostate and NSCL cancer cell lines was altered by HDAC inhibitor treatment. In two out of four cancer cell lines, H460 and DU145, exposure to vorinostat increased the fold change of the gMFI and percentage of cells with PD-L1 expression compared to DMSO-treated cells (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…33 In addition, tumor cells can be eliminated by NK cells through antibody-dependent cellular cytotoxicity (ADCC) if the proper IgG1 monoclonal antibody (mAb) target is present on the surface of tumor cells. 3439 We have previously reported the ability of avelumab to mediate the lysis of a range of human carcinomas in vitro by ADCC in the presence of peripheral blood mononuclear cells (PBMCs) or NK cell effectors. 34,39 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the validated GPCRs activate adenyl cyclase, which converts ATP to cAMP, leading to protein kinase A (PKA) activation. Further analysis of the resistance mechanism using melanoma cell lines and patient tumor samples before treatment, during treatment with vemurafenib or dabrafenib/trametinib, and after relapse suggests the hypothesis that cAMP-mediated resistance may operate in part through a CREBdependent mechanism, a downstream effector of cAMP and PKA (Steven & Seliger, 2016). The study also demonstrated that CREB activity was necessary for drug resistance.…”
Section: The Camp Response Element Binding Protein (Creb)mentioning
confidence: 87%